№1 Упростите выр-е а2xx-3-3xx+5 ба+7а-1+а-3^2 №2 Разложите на множители ас^2-16c b3a^2-6ab+3b^2 №3 Упростите выр-е 3a-a^2^2-a^2a-2a+2+2a7+3a^2 №4 разл

№1 Упростите выр-е а)2x(x-3)-3x(x+5) б)(а+7)(а-1)+(а-3)^2 №2 Разложите на множители а)с^2-16c b)3a^2-6ab+3b^2 №3 Упростите выр-е (3a-a^2)^2-a^2(a-2)(a+2)+2a(7+3a^2) №4 разложите на множители а)81a^4-1 b)y^2-x^2-6x-9

ПОМОГИТЕ СРОЧНО

    b)3a^2-6ab+3b^2 =3(a-b)^2

  • а)2x(x-3)-3x(x+5)=2x^2-6x-3x^2-15x=x^2-21x=x(x-21)

    №4 разложите на множители а)81a^4-1=(9a^2+1)(9a^2-1)=(9a^2+1)(3a+1)(3a-1)

    №3 Упростите выр-е

    (3a-a^2)^2-a^2(a-2)(a+2)+2a(7+3a^2)=9a^2+a^4-6a^3-a^4+4a^2+14a+6a^3=13a^2+14a

    №2 Разложите на множители а)с^2-16c =c(c-16)

    б)(а+7)(а-1)+(а-3)^2=a^2-7+6a+a^2+9-6a=2a^2+2=2(a^2+1)

    b)y^2-x^2-6x-9=y^2-(x+3)^2=(y-x-3)(y+x+3)